The great Imagist in Vela ao crucificado: a study of the language of cinema - Thais Carvalho Fonseca; Jorge Luiz Borges Bezerra (Cadernos de Letras da UFF, 2012)
Cinematographic language is recognized for its capacity for expression and creativity. Through the creation of the camera, in the exhibition, and of the assembly, in the narration, the narrative of the cinema is constructed. In Vela ao Crucificado, a study of the point of view is able to perceive how the great imagist mobilizes language mechanisms, present in the short film of Frederico Machado, in the construction of a discourse that reveals itself paradoxical.